Blockchain as an Instrument for Improving Banking Processes - Bojana Vukovljak (Naše gospodarstvo/Our economy, 2023)
One of the best-known innovations of the recent past is blockchain. Due to its usability, it has generated considerable interest in several economic areas. A decentralised system's approach can potentially reshape existing industries or make them redundant. Such technology can add a new dimension to processes, which is particularly relevant for the banking sector in the future. This demonstrates a great necessity to deal with blockchain with respect to market position and competition. This paper aims to provide insight into the current potential of blockchain applications in banking procedures. The benefits of process improvement in the financial sector are also outlined. This research shows that many experiences and adequate knowledge are already available. According to recent research, this technology will benefit banks’ business models, performance, and capabilities. However, blockchain is still in the phase of research and development, which is a crucial aspect of the banking industry.